Current Guidelines for Gender Affirming Care for Transgender Individuals - Shadianloo, Shervin; Dancyger, Ida; Fornari, Victor (Adolescent Psychiatry, 2022)
Background and Aims: The guidelines for transgender care are evolving and incorporate a multidisciplinary team approach. These roadmaps entail an understanding of gender development, mental health, and sociocultural factors in individual and family lives, as well as the specific medical needs in the process of transitioning and ongoing treatment. New research is continuing to update the best evidence-based practice. Multiple professional health organizations have published guidelines. The World Professional Association of Transgender Health has pioneered the Standard of Care, currently version seven. Other leading organizations have their own publications with an emphasis on specific relevant medical needs. In this paper, The World Professional Association of Transgender Health Standard of Care and the recommendation of multiple psychiatric and pediatric organizations are reviewed to provide an overview. Discussion: Most current guidelines have similar recommendations in providing care for transgender individuals. The more recent data has shown the benefits of medical transitioning in youth and updated recommendations in this age group. Healthcare professionals are encouraged to stay up to date with these current guidelines. Further research is recommended.
Keywords: LGBTQ